2013
DOI: 10.1007/s10995-013-1407-6
|View full text |Cite
|
Sign up to set email alerts
|

Validity of Prepregnancy Weight Status Estimated from Self-reported Height and Weight

Abstract: The Institute of Medicine's gestational weight gain guidelines are intended to reduce pregnancy complications, poor birth outcomes and excessive postpartum weight retention. The specific weight gain guidelines vary by prepregnancy weight status. We evaluated the validity of prepregnancy weight status (underweight, normal weight, overweight and obesity) classified from self-reported prepregnancy height and weight in reference to those from measured data during the first trimester of pregnancy and imputed data f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
115
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(127 citation statements)
references
References 16 publications
7
115
0
Order By: Relevance
“…It was also determined that the use of prepregnancy BMI and Trimester 3 weight provided a realistic extrapolation of expected weights. In combination with literature that suggests that use of self-reported pre-pregnancy weight is a valid measure (Shin et al, 2014), we are confident that pregnancy weight gain was represented accurately in the current sample.…”
Section: Limitationssupporting
confidence: 54%
“…It was also determined that the use of prepregnancy BMI and Trimester 3 weight provided a realistic extrapolation of expected weights. In combination with literature that suggests that use of self-reported pre-pregnancy weight is a valid measure (Shin et al, 2014), we are confident that pregnancy weight gain was represented accurately in the current sample.…”
Section: Limitationssupporting
confidence: 54%
“…Other studies have demonstrated a strong correlation between self-reported and clinically measured pre-pregnancy weight. (24,25) Some participants were lost to follow up (5%), and we accounted for this using an intent-to-treat analysis. We were not able to measure cost-effectiveness in this study.…”
Section: Discussionmentioning
confidence: 99%
“…However, self-reported pre-gravid weight has been shown to agree fairly well with measured weights [15,40,41]. A possible limitation of this meta-analysis may be that most authors did not explicitly report how the IOM criteria were used for classifying excessive GWG.…”
Section: Strengths and Limitationsmentioning
confidence: 92%